Scalable Electrocatalytic Urea Wastewater Treatment Coupled with Hydrogen Production by Regulating Adsorption Behavior of Urea Molecule - Yang, Chunming; Pang, Huijuan; Li, Xiang; Zheng, Xueyan; Wei, Tingting; Ma, Xu; Wang, Qi; Wang, Chuantao; Wang, Danjun; Xu, Bin (Nano-Micro Letters, 2025)
Electrocatalytic urea wastewater treatment technology has emerged as a promising method for environmental remediation. However, the realization of highly efficient and scalable electrocatalytic urea wastewater treatment (SEUWT) is still an enormous challenge. Herein, through regulating the adsorption behavior of urea functional groups, the efficient SEUWT coupled hydrogen production is realized in anion exchange membrane water electrolyzer (AEMWE). Density functional theory calculations indicate that self-driven electron transfer at the heterogeneous interface (NiO/Co3O4) can induce charge redistribution, resulting in electron-rich NiO and electron-deficient Co3O4, which are superior to adsorbing C=O (electron-withdrawing group) and –NH2 (electron-donating group), respectively, regulating the adsorption behavior of urea molecule and accelerating the reaction kinetics of urea oxidation. This viewpoint is further verified by temperature-programmed desorption experiments. The SEUWT coupled hydrogen production in AEMWE assembled with NiO/Co3O4 (anode) and NiCoP (cathode) can continuously treat urea wastewater at an initial current density of 600 mA cm−2, with the average urea treatment efficiency about 53%. Compared with overall water splitting, the H2 production rate (8.33 mmol s−1) increases by approximately 3.5 times. This work provides a cost-effective strategy for scalable purifying urea-rich wastewater and energy-saving hydrogen production. Highlights: 1 The heterogeneous interface of NiO/Co3O4 was constructed for regulating adsorption behavior of urea functional groups. 2 The regulation mechanism of urea molecular adsorption behavior was verified by temperature-programmed desorption experiments and density functional theory calculations. 3 Efficient and scalable electrocatalytic urea wastewater treatment coupled with hydrogen production was realized in anion exchange membrane water electrolyzer AEMWE, which can continuously treat urea wastewater at an initial current density of 600 mA cm-2, with about 53% in average urea treatment efficiency.